Phytochemical Analysis and in vitro Antimicrobial Activity of Extracts from Amorphophallus paeoniifolius (Dennst.) Nicolson and Amorphophallus commutatus (Schott) Engl. corms - Salunke, Chetana Anand; Satpute, Rajendra A (JOURNAL OF ROOT CROPS, 2018)
The increasing antibiotic resistance of different strains of pathogens is a global issue. To fight against this problem best, solution is to use traditional medicine system i.e. use of medicinal plants of our community for disease management and control. This study is focused on exploring the phytochemical and antimicrobial properties of Amorphophallus paeoniifolius and Amorphophallus commutatus corms. For extract preparation, solvents used were methanol, hexane and distilled water. Qualitative phytochemical analysis of corm extracts confirmed the presence of glycosides, saponins, tannins, phenols, flavonoids, carbohydrates and alkaloids. The corm extracts were tested against four bacterial and two fungal pathogens by disc diffusion assay by Kirby Bauer method. The corm extracts of both the Amorphophallus species exhibited inhibitory activity against all the fungal and bacterial pathogens tested. The experiment confirmed the potential of both the species of Amorphophallus studied and hence corms of both the plants can be used for isolation of bioactive compounds and related pharmacological activities.